Generalized pustular psoriasis associated with Epstein–Barr virus. (1st March 2015) - Jiyad, Z.; Moriarty, B.; Creamer, D.; Higgins, E.
Summary: Generalized pustular psoriasis (GPP) is a rare and severe variant of psoriasis. We report a case of a 79‐year‐old woman who presented with generalized pustular psoriasis and significant Epstein–Barr virus (EBV) viraemia. Serial measurements of EBV DNA showed a correlation with the deterioration in her clinical condition. We speculate that EBV reactivation triggered the development of GPP, and propose that further investigation is required into the association between EBV and GPP.